Can probiotics enhance fertility outcome? Capacity of probiotics as a single intervention to improve the feminine genital tract microbiota in non-symptomatic reproductive-aged women - Blancafort, Claudia; Llácer, Joaquín (Frontiers in Endocrinology, 2023)
Modifications in vaginal and endometrial microbiome and microbiota have been associated with fewer implantation rates and poorest pregnancy outcomes. Therefore, its study has emerged as a new biomarker in reproductive medicine. Despite the numerous papers published on probiotic use for vaginal dysbiosis and their actual wide empiric use specially for infertile patients, there’s still no clear answer justifying their recommendation. The impact of probiotics on the vaginal or endometrial microbiota has often been investigated under symptomatic altered vaginal microbial ecosystem, such as bacterial vaginosis. However 50% of women with bacterial vaginosis are asymptomatic. Actual clinical practice guidelines clearly recommend the use of specific antimicrobial agents for the management of symptomatic vaginal infections. Assuming this should be the management as well for infertile population, what should be the treatment for the 50% non-symptomatic women presenting unfavorable vaginal/endometrial microbiota? The aim of this review is to assess the capacity of probiotics as a single intervention to alter the feminine genital tract microbiota in non-symptomatic reproductive aged women.